Fifty 20th Century Artists : in the Scottish National Gallery of Modern Art - Johnstone, Christopher; Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : National Galleries of Scotland)
Arp, Jean ; Blathus ; Bellany, John ; Braque, Georges ; Cambell Boileau Cadell, Francis ; Chia, Sandro ; Davie, Alan ; De Andrea, John ; Derain, André ; Dix, Otto ; Dubuffet, Jean ; Eardley, Joan ; etc.
boek